Uncomplicated Subhepatic Appendicitis: Case Report and Literature Review - Flores-Garcia, A. E.; Ramírez-Vázquez, J. L.; Gonzalez-Dominguez, F. D.; Betanzos-Planell, A. C.; Dominguez-Jimenez, M.; Torres-Huerta, B. (British Journal of Healthcare and Medical Research, 2023)
Introduction: Subhepatic appendicitis symptoms in adults are low in frequency with atypical symptoms, which makes early diagnosis and management difficult. Clinical case: 33-year-old male, with a 24-hour evolution condition characterized by diarrheal evacuations, treated with antibiotics. Subsequently, he presented with vomiting, colicky abdominal pain, and a fever of 39 °C. With a clinical picture compatible with an appendicular process, an exploratory laparotomy was performed with suspicion of an appendicular process in the subhepatic, finding an inflamed appendix, 5 cm long, with an appendectomy. Discussion: Atypical signs and symptoms may be observed. These may include left-sided abdominal pain, which is located in the left upper quadrant. While the appendage on the side left is relatively rare and occurs in approximately 0.02% of the adult population, it is more likely to occur in people with intestinal malrotation or situs inversus. Conclusions: All the anatomical variants of the appendix must be considered due to the multiple clinical presentations, with an atypical presentation and the diagnosis is masked.